Implementation and The Role of The Government in The Imposition of Income Tax (PPh) on Youtubers in Indonesia - Iqry Izza Zakialdy; Ardiantoro Arno Haryanto; Nadzirah Nurul Hanan; Boris Gabe Tobing (Proceeding International Conference Restructuring and Transforming Law, 2023)
Youtube currently seems to have become a very promising profession or job. A YouTuber with a variety of creative content will get income from the videos he uploads. This is seen by the government as a potential sector to be subject to income tax (PPh) which can increase state revenue. This article was written with the aim of finding out how the current implementation is in collecting income tax on YouTubers and to find out the extent of the government's role in implementing income tax collection against YouTubers. The method of writing this article uses a descriptive analytical method with data collection using the literature study method. In Law No. 36 of 2008, it is explained that the object of income tax is any economic addition to the taxpayer. It can be seen that the income of several YouTubers has exceeded the specified non-taxable income (PTKP). Thus YouTubers must be taxed in accordance with the provisions of the applicable laws and regulations. The government as a supervisor in taxation in Indonesia must play a role especially in educating and socializing taxpayers and applicable laws and regulations, especially regarding tax revenue for YouTubers.